PENGARUH PERBEDAAN DOSIS PUPUK PHOSPAT TERHADAP PERTUMBUHAN PHYTOPLANKTON - Sobirin .; Muhammad Agus; Basuki Rahardjo (Pena Jurnal Ilmu Pengetahuan Dan Teknologi, 2013)
This study aims  to  determine the  effect  of  different doses  of phosphate fertilizer on  the  gowth  of phytoplankton.  The  research is  based  on a  completely  randomized  design with 6 treatments  and  3 replications. Treatments were applied as follows: A: 0 g / l, B: 0.25 g / l, C: 0.5 g / l, E: 1 g / l, F: 1.25 g / l. Data previously conducted analysis of variance test for normality and homogeneity of variance analysis test is then performed. While the data of water quality variables were analyzed descriptively. Results of any treatment is A:  Peak phytoplankton gowth occurred at 15.00  hours  to 3 days (168x104)cells, B: Peak phytoplankton gowth occurred at 15:00  hours today to 3 (180x104) cells, C: Peak phytoplankton gowth occurred at  12:00  hours day  3 (226x104)  cells,  D:  Peak phytoplankton gowth occurred at 12:00 hours to 4 days (250x104 ) cells, E: Peak phytoplankton gowth occurred at 12.00 hours to 4 days (346x104) cells, F: Peak of phytoplankton gowth occurred at 12:00 hours to 3 days (242x104)  cells.  Results of  the  analysis  showed that different doses  of the treatment effect is highly significant to the gowth of phytoplankton. Medium quality water throughout the study is still in the range of viable ie 29 oC - 30 oC, DO 6,1 – 7,2 and pH 7- 8.Key Words : Phytoplankton Gowth, Phosphate Fertilizers, Dose